FOXD1 promotes dedifferentiation and targeted therapy resistance in melanoma by regulating the expression of connective tissue growth factor. Issue 3 (6th May 2021) - Sun, Qian; Novak, Daniel; Hüser, Laura; Poelchen, Juliane; Wu, Huizi; Granados, Karol; Federico, Aniello; Liu, Ke; Steinfass, Tamara; Vierthaler, Marlene; Umansky, Viktor; Utikal, Jochen
Abstract: Metastatic melanoma is an aggressive skin cancer and associated with a poor prognosis. In clinical terms, targeted therapy is one of the most important treatments for patients with BRAF V600E ‐mutated advanced melanoma. However, the development of resistance to this treatment compromises its therapeutic success. We previously demonstrated that forkhead box D1 ( FOXD1 ) regulates melanoma migration and invasion. Here, we found that FOXD1 was highly expressed in melanoma cells and was associated with a poor survival of patients with metastatic melanoma. Upregulation of FOXD1 expression enhanced melanoma cells' resistance to vemurafenib (BRAF inhibitor [BRAFi]) or vemurafenib and cobimetinib (MEK inhibitor) combination treatment whereas loss of FOXD1 increased the sensitivity to treatment. By comparing gene expression levels between FOXD1 knockdown (KD) and overexpressing (OE) cells, we identified the connective tissue growth factor (CTGF) as a downstream factor of FOXD1. Chromatin immunoprecipitation and luciferase assay demonstrated the direct binding of FOXD1 to the CTGF promoter. Similar to FOXD1, knockdown of CTGF increased the sensitivity of BRAFi‐resistant cells to vemurafenib. FOXD1 KD cells treated with recombinant CTGF protein were less sensitive towards vemurafenib compared to untreated FOXD1 KD cells. Based on these findings, we conclude that FOXD1 might be a promising new diagnostic marker and a therapeutic target for the treatment of targeted therapy resistant melanoma. Abstract : What's new? In melanoma therapy, resistance to targeted therapeutics such as vemurafenib has emerged as a serious clinical problem. In this study, the authors found that increased expression of an oncogenic transcription factor called 'FOXD1' correlates with a poor prognosis in melanoma patients. They also found that FOXD1 promotes targeted‐therapy resistance in human melanoma cells, by upregulating the expression of the CTGF oncogene. These results indicate that FOXD1 may represent a novel therapeutic target in certain treatment‐resistant melanomas, as well as a useful prognostic biomarker.